STRATEGI PENGELOLAAN SDM DALAM PENINGKATAN KINERJA KARYAWAN BERKELANJUTAN DI ERA DIGITAL PADA KANTOR BADAN PENDAPATAN DAERAH KABUPATEN BENGKALIS - Sufnirayanti,; Sri Wahyuni Zanra, (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2023)
This study aims to analyze the challenges faced by the Regional Revenue Agency of Bengkalis Regency in managing HR in the Digital era and to analyze the implementation of effective and sustainable HR management strategies in the digital era at the Regional Revenue Agency of Bengkalis Regency in continuously improving employee performance. This research is a survey research with mixed methods (mix method). This approach combines the collection and analysis of quantitative and qualitative data to provide a more comprehensive understanding of HR management strategies and improving employee performance in the digital era at the Bengkalis Regency Regional Revenue Agency Office. The results of this study indicate that the challenges faced by the Regency Regional Revenue Agency Office Bengkalis in improving employees' digital skills includes different levels of understanding and technological skills, adapting to technological changes, related to data protection and security in the digital era, transformation of organizational culture, the need to develop HR skills and knowledge in the digital era. Effective and sustainable HR management strategies in the digital era at the Bengkalis Regency Revenue Agency Office can play an important role in improving employee performance in a sustainable manner including identifying skills and competencies needed, skills development and training programs, using appropriate technology and digital tools, building a culture digital innovation and skills development